PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SISTEM REM PADA MATA PELAJARAN PEMELIHARAAN CHASIS DAN PEMINDAH TENAGA - Hafiz Arif Syahriar; Rabiman Rabiman (Jurnal Taman Vokasi, 2017)
The aims of this study is to produce a brake system learning multimedia that feasible for education. This study is Research and Development with Four-D model. The subject of this study is students 10th grade of SMK Muhammadiyah 1 Imogiri which consist of 25 students. There are three phases of validation: Validation of Media Expert, Validation Material Expert, and Validation User. Validation of media expert showing that brake system learning multimedia is very feasible for education with value percentage 88,57%. Validation of material expert showing that brake system learning multimedia is very feasible for education with value percentage 94,17%. Validation user showing that brake system learning multimedia based on flash is feasible with value percentage 76,44%.